The Effectiveness of Pre-Employment Card Program in Encouraging Participation in the Labor Market - Wafi, Faiz Abdullah; Suprayitno, Aziz Wahyu (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2025)
Research Originality — This study uses data from the 2022 National Labor Force Survey (Sakernas) to capture the current impact of the COVID-19 pandemic on the effectiveness of the Pre-Employment Card Program in increasing employment opportunities, as well as to analyze differences in its impact based on gender through interaction variables. Research Objectives — The Pre-Employment Card Program, launched in April 2020, aims to improve workforce competencies, increase workforce competitiveness and productivity, and develop entrepreneurship. This study aims to examine the effectiveness of the Prakerja Card Program in securing employment opportunities. Research Methods — The estimation method used is the Likelihood Binomial Logit, and the data were sourced from the 2022 National Labor Force Survey (Sakernas) conducted by the Statistics Indonesia (BPS). Empirical Results — The results indicate that participation in the Pre-Employment Card Program increases employment opportunities by 0.39 percent. The study also shows that age has an inverted U-shaped relationship with employment opportunities. Additionally, male recipients of the Prakerja Card Program, those who are married, and those with higher levels of education have a greater likelihood of securing employment. Meanwhile, moderation variables indicate that the marginal effect of the Prakerja Card Program on employment opportunities for males is lower compared for women. Implications — Training and job placement monitoring must be reinforced to ensure lasting program benefits. Recipients should be encouraged to adopt a forward-looking vision both as job seekers and creators. Training should also be tailored to age and education, given the inverted U-shaped relationship between age and employment opportunities, which calls for different approaches for youth and older workers.